Identification and characterization of small-molecule modulators that promote cancer cell elimination - Binici, Aylin (Technische Universität Dortmund, 2024)
In this doctoral thesis, two strategies were used to fight cancer. The first strategy aimed to eliminate cancer via natural killer (NK) cells. Within the tumor microenvironment (TME), cancer cells and the cancer-supporting tissue hijack immunosuppressive pathways, leading to the increased secretion of immune inhibitory factors that aid tumor progression, ultimately leading to the evasion of NK-cell mediated eradication of cancer cells. A phenotypic co-culture assay was optimized to mimic the TME. The assay consists of a human lung adenocarcinoma cells A549, primary lymphocytes, and immunomodulatory factors. This setup was used to screen a library of 29,502 small molecules in search of compounds that can restore NK cell-mediated cancer cell elimination. The second strategy was focused on eliminating cancer through indirect targeting of the small GTPase Kirsten rat sarcoma (KRas). KRas is mutated in approximately 17 % of all solid tumors, and current FDA-approved drugs solely target its G12C mutant. The activity of this oncoprotein depends on its localization to the plasma membrane, and within the cell, its translocation within the cell is facilitated by its interaction with the prenyl group-binding chaperone retinal rod rhodopsin-sensitive cGMP 3',5'-cyclic phosphodiesterase subunit delta (PDEδ). Therefore, instead of directly targeting KRas, the covalent inhibitor Deltacovalin was designed to target PDEδ.

Im Rahmen dieser Doktorarbeit wurden zwei Strategien zur Bekämpfung von Krebs verwendet. Der erste Ansatz zielte darauf ab, Krebs durch NK Zellen zu eliminieren. In der Tumormikroumgebung (TMU), nutzen Krebszellen und das umgebende unterstützende Gewebe immuninhibierende Signalwege, die das Wachstum von Tumoren fördern und dadurch die NK Zell-vermittelte Eliminierung von Krebszellen inhibieren. Um eine Substanzbibliothek bestehend aus 29,502 Substanzen zu testen wurde ein phänotypisches TMU-nachahmendes Testverfahren bestehend aus der humanen Lungenkrebszelllinie A549, primären Lymphozyten und immunmodulierenden Faktoren optimiert. Ziel dieses Testverfahrens war es Verbindungen zu identifizieren, die die NK Zell-vermittelte Krebszelleliminierung begünstigt. Im Fokus der zweiten Strategie lag die Bekämpfung von Krebs über die kleine GTPase KRas, die in etwa 17 % aller Tumoren mutiert ist. Gegenwärtig sind die von der FDA zugelassenen Medikamente ausschließlich auf die G12C Mutante fokussiert. Die Aktivität von KRas wird durch seine Lokalisierung an der Plasmamembran ermöglicht. Für die Translokation von KRas innerhalb der Zelle ist die Interaktion mit PDEδ essentiell. Daher wurde eine kovalente Substanz mit dem Namen Deltacovalin entwickelt, um die Aktivität von KRas indirekt über die Inhibierung des Interaktionspartners PDEδ zu hemmen.
Keywords: Antitumor agents; Biological activity; Immunology; Natural killer cells; Screening; Small molecules; Tumor microenvironment; PDEδ; KRas signaling; 570; 540; Immunologie; Pharmazeutische Chemie; Tumor